2004
DOI: 10.1016/j.febslet.2004.11.101
|View full text |Cite
|
Sign up to set email alerts
|

Expression and subcellular targeting of canine parvovirus capsid proteins in baculovirus‐transduced NLFK cells

Abstract: A mammalian baculovirus delivery system was developed to study targeting in Norden Laboratories feline kidney (NLFK) cells of the capsid proteins of canine parvovirus (CPV), VP1 and VP2, or corresponding counterparts fused to EGFP. VP1 and VP2, when expressed alone, both had equal nuclear and cytoplasmic distribution. However, assembled form of VP2 had a predominantly cytoplasmic localization. When VP1 and VP2 were simultaneously present in cells, their nuclear localization increased. Thus, confocal immunofluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 73 publications
0
8
1
Order By: Relevance
“…In this study, the IFA showed that the rCDV-VP2-expressed VP2 was primarily localized in the nucleus, as evidenced by a green (Alexa Fluor ® 488)-blue (DAPI) merged morphology in Figure 1E (the first panel). This was in contrast with another conclusion in a previous report, which displayed that nuclear transport of CPV VP2 in the assembled form was hampered in the absence of other viral components (Gilbert et al, 2005). Yuan and Parrish (2001), nevertheless, showed that the VP2, albeit expressed alone, could accumulate in the nucleus of the A72 cell (Yuan and Parrish, 2001).…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, the IFA showed that the rCDV-VP2-expressed VP2 was primarily localized in the nucleus, as evidenced by a green (Alexa Fluor ® 488)-blue (DAPI) merged morphology in Figure 1E (the first panel). This was in contrast with another conclusion in a previous report, which displayed that nuclear transport of CPV VP2 in the assembled form was hampered in the absence of other viral components (Gilbert et al, 2005). Yuan and Parrish (2001), nevertheless, showed that the VP2, albeit expressed alone, could accumulate in the nucleus of the A72 cell (Yuan and Parrish, 2001).…”
Section: Discussioncontrasting
confidence: 99%
“…structure/function relationships at the molecular/cellular levels have been carried out. These include deletions of [33] and epitope insertions in the loops of the virion [34], N-terminal fusion of foreign antigens to VP1 [35,36], N-terminal insertion and fusion [17,19,37] or deletions of VP2 [33,38], and C-terminal fusions to VP2 [34,37,39]. …”
Section: Discussionmentioning
confidence: 99%
“…Norden Laboratories feline kidney (NLFK) [93] [26]. This notion is supported by the finding that direct injection of nucleocapsids into cytoplasm does not affect the nuclear import, which implies that endosomal escape is not necessarily a critical step [27].…”
Section: Feline Cellsmentioning
confidence: 86%
“…For example, the efficient baculovirus transduction of liver cells is exploited to deliver the genomes of hepatitis B and C viruses [89,90] into hepatoma cell lines, and is harnessed to evaluate the efficacy of antiviral compounds [91,92]. The low baculovirus cytotoxicity is tackled for the subcellular targeting of canine parvovirus capsid proteins [93] and viral membrane proteins [94] in baculovirustransduced cells, and more importantly, for the development of cell-based assays in the drug discovery setting (for review see [95][96][97]). The baculovirus display technology is utilized to construct eucaryotic epitope libraries (for review see [98,99]) and generate monoclonal antibodies [100,101].…”
Section: Applications Of Baculovirus-mediated Gene Deliverymentioning
confidence: 99%